High temperature stability study of carbon supported high surface area catalysts—Expanding the boundaries of ex-situ diagnostics. (1st September 2016) - Polymeros, G.; Baldizzone, C.; Geiger, S.; Grote, J.P.; Knossalla, J.; Mezzavilla, S.; Keeley, G.P.; Cherevko, S.; Zeradjanin, A.R.; Schüth, F.; Mayrhofer, K.J.J.
Graphical abstract: Highlights: Suggestion of strategy to effectively characterize the stability of HSACs ex-situ. High temperature stability study utilizing comprehensive toolbox approach. Disentangling of different mechanisms that contribute to Pt/C degradation. Suggestion of strategy to stabilize Pt catalyst by tuning the electrode morphology Abstract: The performance of proton-exchange membrane fuel cells (PEMFCs) is defined by the equally important parameters of the intrinsic activity and stability of the electrocatalysts. This work focuses on the stability of carbon supported high surface area oxygen reduction reaction catalysts at potentials and temperatures similar to the operating conditions of PEMFCs. The catalysts used for this investigation consist of Pt nanoparticles of the same particle size supported on two types of carbon support having different textural properties, i.e., Vulcan and Hollow Graphitic Spheres (HGS). A broad toolbox of characterization techniques is utilized at 60 °C in order to resolve the contribution of the different degradation mechanisms, namely nanoparticle coalescence, metal dissolution and the corrosion of carbon support, to the total active surface area loss. The results obtained by investigating the impact of temperature, potential treatment and catalyst layer morphology on the aging behavior lead to a deeper understanding of the aging mechanisms and their interrelation at application-relevant conditions. Moreover, the previously reported improved performance of the Pt/HGS catalyst is confirmed also under higher temperatures. The experimental approach introduced in this work, highlights new challenges for high-temperature degradation investigations with supported PEMFC catalyst.